2014
DOI: 10.1002/jps.23932
|View full text |Cite
|
Sign up to set email alerts
|

Orally Administered DTPA Penta-Ethyl Ester for the Decorporation of Inhaled 241Am

Abstract: Diethylenetriaminepentaacetic acid (DTPA) is an effective decorporation agent to facilitate the elimination of radionuclides from the body, but its permeability-limited oral bioavailability limits its utility in mass-casualty emergencies. To overcome this limitation, a prodrug strategy using the penta-ethyl ester form of DTPA is under investigation. Pharmacokinetic and biodistribution studies were conducted in rats by orally administering [14C]DTPA penta-ethyl ester, and this prodrug and its hydrolysis product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…C2E5, a lipophilic compound with a CLogP value of 4.7, was hydrolyzed by recombinant protein CES1 and CES2 7 . Hydrolysis of C2E5 by CES1 was higher than CES2 at an enzyme concentration of 1mg/ml (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C2E5, a lipophilic compound with a CLogP value of 4.7, was hydrolyzed by recombinant protein CES1 and CES2 7 . Hydrolysis of C2E5 by CES1 was higher than CES2 at an enzyme concentration of 1mg/ml (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The five added ester moieties greatly increase the lipophilicity of DTPA, which is measured by increased CLogP. (CLogP of -2.7 for DTPA in contrast to ClogP of 4.7 to C2E5) Studies in rats confirmed that C2E5 shows enhanced oral bioavailability compared to DTPA, with extensive but incomplete metabolism 7 and can elicit effective radionuclide decorporation following oral 8 and transdermal delivery 9 . Together, these findings suggest that this prodrug may be a useful and effective alternative treatment to DTPA.…”
Section: Introductionmentioning
confidence: 99%
“…The liver, spleen, kidneys, lungs and both femurs were among the tissues collected and analyzed for radioactivity. Samples were thermally and chemically processed as previously described (Sueda et al, 2014), placed into 20-mL scintillation vials and the gamma pulse height from 241 Am was analyzed in a gamma counter (2480 Wizard 2 Gamma Counter, Perkin Elmer, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…These were the penta-ethyl and di-ethyl esters of DTPA, referred to as C2E5 and C2E2, respectively. C2E5 was shown to effectively decorporate 241 Am in a wound-contamination animal model (Sueda et al, 2012), (Sueda, 2014), but its unfavorable pharmaceutical properties and concerns related to its hepatotoxicity caused us to focus our efforts on C2E2.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, shortly after injection DTPA is in a large excess (factor 10 4 -10 5 ) compared to plutonium ions. The binding constant of DTPA for tetravalent plutonium has been reported to be about 10 30 (log K = 29.5) [26] and 10 23 at physiological conditions (log K = 23.4) [27]. Since the chelating agent is in vast access of the radionuclide and has high binding affinity, we can reasonably assume that shortly after the injection of 1 g DTPA, virtually all of the plutonium present in the central compartment is bound at the activities studied in this paper.…”
mentioning
confidence: 99%